Ethnography and Craft Knowledge - Atkinson, Paul (Qualitative Sociology Review, 2013)
The paper has twin themes: the creative work of ethnographic interpretation, and the ethnographic interpretation of creative work. Illustrated with reference to recent and current fieldwork on craft, dance, and opera, it suggests some ways in which the ethnographer might creatively engage with her or his chosen fields. It criticizes the current view of “grounded theory,” which is found to be far too procedurally driven, in favor of more creative explorations of data.